ANALISIS KELAYAKAN FINANSIAL USAHATANI JERUK SIAM GUNUNG OMEH (Citrus microcarpa L.) (STUDI KASUS NAGARI KOTO TINGGI KECAMATAN GUNUNG OMEH KABUPATEN LIMA PULUH KOTA PROVINSI SUMATERA BARAT) - Rista Chintya Dewi Sumartono; Suardi Tarumun; Jum'atri Yusri (Indonesian Journal of Agricultural Economics, 2019)
This research aimed to analyze the financial feasibility and sensitivity to price changes of the input and output of jeruk Siam Gunung Omeh farming in Nagari Koto Tinggi Gunung Omeh District Lima Puluh Kota Regency Province of Sumatera Barat. A survey was conducted to collect primary and secondary data. Data was analyzed by using investment criteria that is Net Present Value (NPV), Net Benefit Cost Ratio (Net B/C), Internal Rate of Return (IRR) and Payback Period (PP). The results showed that jeruk Siam Gunung Omeh farming is economically feasible because it has a positive NPV value of IDR 984.579.113,- Net Benefit Cost Ratio is greater than one (6,53), IRR value is greater than Social Opportunity Cost of Capital (SOCC), with a long return on investment or Payback Period (PP) for 5 years 9 months, is less than the business period of 15 years. Siam orange farming is still eligible to go if there is an increase in input and output price decrease of 10% and 20%.